Exploring Theoretical Constructs in Leadership Excellence: A Multidimensional Framework - Yayha, Mohammed AbulJaber; Kamil, Saif Ali; Barakat, Maha; Alkabi, Hameed Salim (Journal of Ecohumanism, 2024)
Background: Leadership theories, notably transformational, servant, and authentic, play an important role in creating organizational dynamics. Recognizing the complexities of leadership, this study examines the fundamental aspects and comparative effectiveness of different theories. Objective: The article aims to identify the main elements of transformational, servant, and authentic leadership theories and examine their empirical effects on organizational results. Methods: A systematic review was undertaken, with papers retrieved from Scopus, Web of Science, and EBSCO databases from 2017 to 2021. Keywords relating to the three leadership philosophies aided the search. To ensure the inclusion of relevant empirical studies, rigorous selection criteria were used. The study used a multi-staged method, including quantitative content analysis and statistical modelling, to investigate the prevalence and influence of certain leadership constructs. Results: Transformational leadership places a strong emphasis on 'Idealized Influence', 'Inspirational Motivation', and 'Intellectual Stimulation', whereas servant leadership prioritizes 'Empowerment' and 'Community Service'. Authentic leadership was intimately linked to self-awareness' and relational transparency'. Statistical investigations revealed that these constructs improve employee satisfaction and organizational performance. Conclusion: This study advances our understanding of leadership excellence by rigorously comparing theoretical elements and their practical applications. It demonstrates the separate but complementary characteristics of transformational, servant, and authentic leadership, with each contributing distinctively to achieving leadership excellence in different organizational situations.